Analysis and Strategic Planning of Information Systems Using the Adm Togaf Framework - Wilda Santika; Yulhendri Yulhendri (Jurnal Indonesia Sosial Teknologi, 2024)
The Open Group Architecture Framework (TOGAF) method was used in this study to evaluate and plan the information system strategy for PT Telekomunikasi Witel West Jakarta. The background of this research is the need for companies to improve the effectiveness and efficiency of data-driven decision-making and operational monitoring. The research uses TOGAF to assess current conditions, identify key problems, and create architectural solutions that support the company's strategic goals. This research was carried out through several stages, including needs analysis, architectural planning, and solution evaluation. Research shows that the implementation of TOGAF can help companies build a more integrated and responsive monitoring information system to changes that occur in business. This study finds that the TOGAF approach provides a complete framework for planning and managing the transformation of sustainable information systems in companies.